Effective recovery of trans-resveratrol from the leaching solution of muscat grape pomace by developing a novel technology of foam fractionation. (January 2019) - Wu, Zhaoliang; Li, Na; Zhang, Xin; Xu, Yanyan; Shu, Ting; Liu, Wei; Hu, Bin
Abstract: Resveratrol (2, 5, 4′-trihydroxystilbene) is a naturally occurring phytoalexin produced by some spermatogphytes and it has recently attracted the increasing attention of agronomists and pharmacologists owing to its satisfactory bioactivities. The objective of this work was to develop a cost-effective technology of foam fractionation to recover trans -resveratrol ( trans -Res) from the leaching solution of muscat grape pomace on the assistance of molecular imprinting modified SiO2 nanoparticles. First, trans -Res was leached from muscat grape pomace through the method of alkaline extraction. Under the suitable leaching conditions, the leaching yield of trans -Res reached 84.34%. Adsorption experiments were performed for describing the adsorption behavior of trans -Res on the molecular imprinting modified SiO2 nanoparticles. Results indicated that their adsorption could be fairly described by Freundlich model and fitted well with the pseudo-second-order kinetics model. Moreover, the molecular imprinting modified SiO2 nanoparticles could effectively maintain the stability of trans -Res through avoiding the cis-trans photo-isomerization and oxidative degradation. Finally, foam fractionation was carried out for recovering trans -Res from the leaching solution, in which the concentration of trans -Res was as high as 29.09 mg/L. The molecular imprinting modified SiO2 nanoparticles were used as the collector. Under the suitable conditions of loading liquid volume 250 mL, particle size of molecular imprinting modified SiO2 nanoparticles 436.0 nm, sapindus saponin concentration 0.075 g/L, volumetric gas flow rate 100 mL/min and pore diameter of gas distributor 0.180 mm, the enrichment ratio and the recovery percentage of trans -Res reached 13.68 ± 1.03 and 89.73 ± 3.57%, respectively. This work is expected to provide a new technology for selectively recovering non-surface-active materials from the solution with their isomers or analogues, and to facilitate the industrialization of foam fractionation. Highlights: Foam fractionation was used to recover trans -RES from muscat grape pomace. Molecular imprinting modified SiO2 nanoparticles was used as the collector. Adsorption isothermal equation and adsorption kinetics model were determined. The collector can effectively maintain the stability of trans -Res.